Avaliação técnica do desempenho da compensação reativa shunt capacitiva aplicada à expansão de sistemas elétricos - Fabricio Silveira Chaves (2007)
This work presents a strategy for definition of the Capacitive Shunt Reactive Compensation applied to Power Systems Expansion activities. The reactive compensation brings some benefits for electrical systems: greater and better exploitation of the existing electrical system, power factor correction and adequate voltage profile. Besides, this is an attractive expansion alternative regarding economic aspects. The problem involved with reactive compensation is not trivial and the expansion plan preparation becomes a complex task, fact that justifies the great interest of the electric sector in the development of Control Strategies. The definition of the reactive compensation becomes still more complex when a better quality of energy is desired, without voltagecollapse, overvoltage and overcurrent problems and with small harmonic distortion of voltage and current waves. These problems result in damage for energy companies, consumers and electrical power system sector. Expansion planning tasks considers the following steps: (i) Power System Diagnosis Evaluation, in order to detect any deficiency; (ii) Reactive Compensation Equipment Definition; (iii) Economical and Technical Evaluation of the alternatives; (iv) Selection of the most adequate alternative and Preparation of the Expansion Plan. In this work, the procedures related to the technical evaluation of alternatives are defined and detailed. This evaluation is realized by the analysis of the electrical system behavior with respect to the following aspects: voltage stability, by the use of PV and QV curves; electromagnetic transient, where simulations of switching capacitors for critical buses are done; harmonic, where the distortions of the voltage and current wave forms, amplified by the suggested compensation, are verified. The thesis presents also specific procedures for compensation alteration, if the evaluation step indicates this necessity. Three procedures are detailed in this work: Individual, Global and Extended Optimized. Application results of the proposed strategy in real electric networks are presented, in way to demonstrate and illustrate the steps of the procedures.